Comparison Study of PHBA-intercalated Mg/Al-LDH and PHBA-immobilized Mg/Al-LDH: Characterization and Application for [AuCl4]̄ Removal from Solution - Lutfi Aditya Hasnowo; Sri Juari Santosa; Bambang Rusdiarso (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2020)
Synthesis of p-hydroxybenzoic acid (PHBA)-intercalated Mg/Al-LDH and PHBA-immobilized Mg/Al-LDH have been conducted. PHBA-intercalated Mg/Al-LDH hybrid was synthesized by co-assembly process of Mg/Al-LDH nanosheets and PHBA anions. PHBA-immobilized Mg/Al-LDH was prepared by indirect synthesis, where PHBA anions were attached on surface of the Mg/Al-LDH material. Characterization by X-ray Diffraction showed that the PHBA-intercalated Mg/Al-LDH hybrid has the lattice parameter of a=3.02 Å, lattice parameter of c=46.77 Å and basal spacing d003=15.14 Å, where PHBA has been intercalated in interlayer of the hybrid. The PHBA-immobilized Mg/Al-LDH has lattice parameter of a=3.06 Å, lattice parameter of c=23.70 Å and basal spacing d003=7.90 Å. The analytical result confirmed that PHBA has been attached on surface of the hybrid for PHBA-immobilized Mg/Al-LDH. The optimum 10 mL of [AuCl4]‾ 100 mg L-1 removal condition of both hybrids were reached at pH 3. The optimum interaction time of [AuCl4]‾ and PHBA-intercalated Mg/Al-LDH hybrid was 250 minutes, respectively, while that for [AuCl4]‾ and PHBA-immobilized Mg/Al-LDH was 150 minutes. Removal of [AuCl4]‾ by PHBA-intercalated Mg/Al-LDH hybrid followed pseudo second order kinetic, whereas by PHBA-immobilized Mg/Al-LDH followed pseudo first order kinetic. Characterization using stereo photomicroscope confirmed that [AuCl4]‾ could be reduced to Au metal by both hybrids.